Language, Meaning, and Pedagogy: An Analysis of Derivational and Compounding Morphology in Khalil Gibran’s Poetry - Listyowati, Rini; Daril Hanna, Ina; Hamdani, Beny; Haida Umiera Hashim (Universitas Sulawesi Barat, 2025)
In the current research, complex relationship between meaning, language, and pedagogy was seen by examining derivational bound morphemes and compound words used in the poems of Khalil Gibran. Khalil Gibran's poetry uses linguistic frameworks with profound meaning and makes use of spirituality, love and values-oriented themes. The research will establish how the derivational bound morphemes and the compound words selected by Khalil Gibran can enhance the depth meanings of his poems and enhance his expression. Structural descriptive linguistics is the research approach employed in this work since it analyzes specific poems by Gibran, particularly the morphological processes of his poetical language. With the use of literary analysis and linguistic structure in data analysis, this research indicated that usage of compound words and derivational bound morphemes contributes to aesthetic effect and serves as a pedagogical tool for grasping intricate emotional and philosophical concepts. Morphological analysis may uncover additional inside meaning and assist in preserving more appreciation of Gibran's work as an artist. This research adds to advance knowledge of the connection between literature and language, for example, morphology constructs meaning in poetry. This research supports interdisciplinary practice that provides scope for linguistic analysis as augmented by literary interpretation thus enhancing the learning of poetry and language arts